Global Estimates of Ambient Fine Particulate Matter Concentrations from Satellite-Based Aerosol Optical Depth: Development and Application - van Donkelaar, Aaron; Martin, Randall V.; Brauer, Michael; Kahn, Ralph; Levy, Robert; Verduzco, Carolyn; Villeneuve, Paul J. (Environmental health perspectives, 2010)
BACKGROUND: Epidemiologie and health impact studies of fine particulate matter with diameter < 2.5 um (PM₂.₄) are limited by the lack of monitoring data, especially in developing countries. Satellite observations offer valuable global information about PM₂.₄ concentrations. OBJECTIVE: In this study, we developed a technique for estimating surface PM₂.₄ concentrations from satellite observations. METHODS: We mapped global ground-level PM₂.₄ concentrations using total column aerosol optical depth (AOD) from the MODIS (Moderate Resolution Imaging Spectroradiometer) and MISR (Multiangle Imaging Spectroradiometer) satellite instruments and coincident aerosol vertical profiles from the GEOS-Chem global chemical transport model. RESULTS: We determined that global estimates of long-term average (1 January 2001 to 31 December 2006) PM₂.₄ concentrations at approximately 10 km x 10 km resolution indicate a global population-weighted geometric mean PM2.5 concentration of 20 ug/m³. The World Health Organization Air Quality PM₂.₄ Interim Target-1 (35 Hg/m 3 annual average) is exceeded over central and eastern Asia for 38% and for 50% of the population, respectively. Annual mean PM₂.₄ concentrations exceed 80 ug/m 3 over eastern China. Our evaluation of the satellite-derived estimate with ground-based in situ measurements indicates significant spatial agreement with North American measurements (r = 0.77; slope = 1.07; n= 1057) and with noncoincident measurements elsewhere (r = 0.83; slope = 0.86; n = 244). The 1 SO of uncertainty in the satellite-derived PM₂.₄ is 25%, which is inferred from the AOD retrieval and from aerosol vertical profile errors and sampling.The global population-weighted mean uncertainty is 6.7 ug/m³. CONCLUSIONS: Satellite-derived total-column AOD, when combined with a chemical transport model,provides estimates of global long-term average PM₂.₄ concentrations.